Investigating the Impact of Yeasts Additives on the Quality of the RedWines: Autolyzes of Yeast and Yeast Derivatives Introduced During Alcoholic Fermentation - Kazumyan, K. N.; Mikayelyan, M. N.; Gevorkyan, E. R.; Jraghatspanyan, A. A. (ՀԱԱՀ հիմնադրամ)
The second part of the article series is about the study of the influence of yeast and autolyzed yeast derivative on red wines’ qualitative and quantitative characteristics. Wine samples in which the preparation process was explained in the first part of the article were investigated. Wine coloring and phenolic compounds were measured. Organoleptic properties of the wines are presented as spider graphs with tasting notes.
Keywords: Food Science and Technology